Distinguishing Invasive from Chronic Pulmonary Infections: Host Pentraxin 3 and Fungal Siderophores in Bronchoalveolar Lavage Fluids - Dobiáš, Radim; Jaworská, Pavla; Skopelidou, Valeria; Strakoš, Jan; Višňovská, Denisa; Káňová, Marcela; Škríba, Anton; Lysková, Pavlína; Bártek, Tomáš; Janíčková, Ivana; Kozel, Radovan; Cwiková, Lucie; et al. (Journal of fungi, 2022)
The multiple forms of pulmonary aspergillosis caused by Aspergillus species are the most common respiratory mycoses. Although invasive, the analysis of diagnostic biomarkers in bronchoalveolar lavage fluid (BALF) is a clinical standard for diagnosing these conditions. The BALF samples from 22 patients with proven or probable aspergillosis were assayed for human pentraxin 3 (Ptx3), fungal ferricrocin (Fc), and triacetylfusarinine C (TafC) in a retrospective study. The infected group included patients with invasive pulmonary aspergillosis (IPA) and chronic aspergillosis (CPA). The BALF data were compared to a control cohort of 67 patients with invasive pulmonary mucormycosis (IPM), non-Aspergillus colonization, or bacterial infections. The median Ptx3 concentrations in patients with and without aspergillosis were 4545.5 and 242.0 pg/mL, respectively (95% CI, p < 0.05). The optimum Ptx3 cutoff for IPA was 2545 pg/mL, giving a sensitivity, specificity, positive predictive value (PPV), and negative predictive value (NPV) of 100, 98, 95, and 100%, respectively. The median Ptx3 concentration for IPM was high at 4326 pg/mL. Pentraxin 3 assay alone can distinguish IPA from CPA and invasive fungal disease from colonization. Combining Ptx3 and TafC assays enabled the diagnostic discrimination of IPM and IPA, giving a specificity and PPV of 100%.